THE IMPLEMENTATION OF NATURAL DISASTER MANAGEMENT PROGRAM IN INDONESIA BETWEEN 2007 AND 2013 - Heribertus Jaka Triyana (Fakultas Hukum Universitas Gadjah Mada, 2013)
This article focuses on the implementation of the natural disaster management program (NDMP) after the promulgation of Act No. 24 of 2007 on Disaster Management. This implementation will be viewed both from legal and political frameworks. The aim of this article is twofold: First, to assess whether the community-based natural resources management system principle in Act No. 24 of 2007 has been implemented as the core principle for executing the NDMP. Second, to evaluate the hindrance caused by political decentralization to the effective implementation of the NDMP under Act No. 24 of 2007 as taken by local governments under the community-based natural resources management system principle. Artikel ini fokus pada pelaksanaan program penanggulangan bencana alam setelah diundangkannya Undang-Undang Nomor 24 Tahun 2007 tentang Penanggulangan Bencana dengan menggunakan perspektif kerangka hukum dan politik. Tujuan artikel ini ada dua: Pertama, untuk menilai apakah prinsip pengelolaan sumberdaya alam berbasis masyarakat dalam Undang-Undang Nomor 24 Tahun 2007 telah diimplementasikan sebagai prinsip inti untuk melaksanakan program penanggulangan bencana alam tersebut. Kedua, untuk mengevaluasi kendala yang disebabkan oleh desentralisasi politik terhadap keefektifan pelaksanaan program penanggulangan bencana alam menurut Undang-undang Nomor 24 Tahun2007 sebagaimana ditempuh oleh pemerintah daerah di bawah prinsip sistem pengelolaan sumber dayaalam berbasis masyarakat.